A Guide for the Creativity in Modifying Problem-Solving Based Learning Media of Students of IKIP-PGRI Pontianak - Erni Fatmawati; Zainal Arifin (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
This research aimed to 1) describe students’ creativity in modifying problem-solving based learning media, 2) develop a guide for students’ creativity in modifying problem-solving based learning media, and 3) assess the accuracy of usage of the guide for students’ creativity in modifying problem-solving based learning media. It employed a research and development method and a research design which was adapted from Borg and Gall’s model. The subject of research was a group of college students in semester VI academic calendar 2017/2018 who were taking micro-teaching courses in IKIP PGRI Pontianak. Data were collected using observation and questionnaires. The data were analysed using a series of interactive model analysis: data reduction, data presentation, and conclusion drawing. The results showed that: 1) a guide for students’ creativity in modifying problem-solving based learning media was well developed according to pre-planned stages; 2) the students’ creativity in modifying problem-solving based learning media were in “good” category; and 3) the usage of the guide for students’ creativity in modifying problem-solving based learning media was deemed appropriate as 60% students managed to modify their learning media. Keywords: guide, creativity, learning media, problem-solving